The Effect of Multiple Intelligences Based Teaching on the Achievement in the Social Studies Course and the Development of Critical Thinking Skills among the Ninth Grade Female Students in the United Arab Emirates - Abdullah, Raeda Sobhi Youssef; Abu Sneineh, Odeh AbdelGawad (Journal of Curriculum and Teaching Methodology, 2023)
This study aims to highlight the effect of multiple intelligences-based teaching on the achievement of the ninth-grade female students in the social studies course and the development of critical thinking skills in the United Arab Emirates. To achieve this objective, the researcher used quasi-experimental design, where the non-probability sample included (48) female students in Taryam American Private School in Sharjah, UAE, who are randomly divided into two classes: experimental (24), controlled (24). To achieve the objective of the study, the educational material was prepared according to multiple intelligences-based teaching strategies, and two study tools were prepared: the achievement test and the critical thinking skills test. To ensure validity of the content, the two tests and the teacher’s book were checked by ten rulers.The achievement test included (30) paragraphs with difficulty coefficients ranging from (0.37 to 0.67), and from (0.33 to 0.53) for the discrimination coefficient. The other test tool is critical thinking tool, and the two tests were applied to a pilot sample of (30) female students. The reliability of tools was (0855) for the achievement test and (0.914) for the critical thinking test using Kuder-Richardson formula 20 (KR-20).The study concluded that there is a deference with statistical significance at the level of (a=0.05) between the students’ average degree in achievement tests in the social studies course and critical thinking in favor of the experimental group who studied using multiple intelligence-based teaching strategies.
Keywords: Social Studies; Multiple Intelligences; Achievement; Critical Thinking Skills; Grade 9